Análisis de la Recaudación del Impuesto a la Renta del cantón Yantzaza, periodo 2021-2022. - Camacho Tene, Daniela Carolina (2023)
The present Curricular Integration Work called "Analysis of the Income Tax Collection of Yantzaza Canton, period 2021-2022" was carried out as a preliminary requirement to obtain the degree of Bachelor in Accounting and Auditing according to Art. 229 of the Academic Regime Regulations of the National University of Loja, for which we proceeded to identify and compare through tables and figures the main taxes with their collected values and their corresponding percentage variation in the canton during the period 2021- 2022, in order to evaluate the compliance of taxpayers in terms of tax payment, investigate the number of companies that comply with their tax obligations and those that do not, as well as the reasons behind non-compliance and demonstrate transparency in the management of public resources. In order to fulfill the objectives set out in the work, different bibliographic sources such as books, rules, regulations, laws and the official website of the Internal Revenue Service were used, which helped to obtain the necessary information about the existing taxes in Ecuador; and in particular, in the Yantzaza canton, using the methods and techniques necessary to meet the objectives and support the results presented; in effect, resulting in the three main taxes that obtained the highest collection were: Withholdings at the Source with a total of $ 15. 298,015.77 in the year 2021 and $ 28,763,630.77 in the year 2022, followed by Corporate Income in 2021 with a value of $ 55,058.10 and $ 29,783,287.07 in the year 2022, in the same way the Corporate Income Tax indicated a total value of $ 162,049.54 in the year 2021, while for the year 2022 it was $ 346,880.96. Thus, it is concluded that the Yantzaza canton is slightly increasing its income every year due to the excellent tax culture on the part of the taxpayers of the local companies that are individuals or legal entities that have the legal obligation to contribute financially to the State.